State of the Art Competitive Advantage at Indonesia - Harry Fauzan Muhamad Taufiq; Herwan Abdul Muhyi; Pratami Wulan Tresna (Universitas KH. Abdul Chalim Mojokerto, 2025)
Everything a company does exceptionally well compared to its competitors is its competitive advantage, which is essential for its survival. Competitive advantage is one of the key factors that determine the success of a company and a country's economy. In Indonesia itself, competition is prevalent in every industry, encompassing Small and Medium Enterprises (SMEs) and the tourism industry, the above also necessitates the presence of skilled employees at different levels, in addition to technical staff. This article aims to assist researchers in developing a theoretical framework and guiding newcomers in competitive advantage research by providing recommendations on relevant journals and authors to reference when exploring this subject. The study uses the Scopus database to analyze annual research, publication trends, and the most cited documents, as well as to conduct bibliometric analysis. This includes examining grouped research topic trends, publication trends of discussed topics, and researching topics that are still not widely discussed.